(untitled) (Journal of Accounting and Financial Studies ( JAFS ), 2024)
The current research aims to identify the impact of information technology on entrepreneurial performance from the point of view of managers in the General Company for Electronic Systems, in addition to observing the company’s level of interest in the research variables. Hence, the importance of the research became clear through the role performed by the research variables, especially information technology, which contributes to speed Decision making and helping to complete work to achieve pioneering performance as a guarantee for the survival and continuity of the organization. The research adopted the descriptive analytical approach using the questionnaire as a tool for collecting primary data related to the research, in addition to personal interviews, so the community sample was a comprehensive inventory of all senior levels. In the company, the research sample reached (87) people, including (General Manager, Assistant General Manager, Department Managers, Unit and Division Officials), and (71) valid questionnaires were retrieved, meaning a percentage of (81%). In order to statistically process the research data, then use statistical programs ( SPSS V.26 ) and descriptive statistics methods to test the research hypotheses. The results concluded that there is a significant effect of the independent variable, information culture, on the dependent variable, entrepreneurial performance. The results of the research, represented by some conclusions, indicated that the senior management in the researched company has a perception of the importance of information technology and is keen to The company will be better than it is, in addition to the company’s management’s interest in working to connect the company with other companies and organizations related to communication networks for the purpose of exchanging information between departments and rapid response in providing services